Development of Video Learning Materials for Asertification of Communication Skills in Students - Yonny Chintya Hasty Syafutry; Muhammad Ali; Bunga Ayu Wulandari (Postgraduate, University of Mataram, 2024)
The aim of this research is to determine the effectiveness of developing assertive learning videos for Jambi University students. The research method used in this research is the Research and Development (R&D) method. This development research uses the development method from Trollip and Allesi which centers on the use of multimedia as a learning tool. This method was chosen because it can be used as a guide for developing and testing the effectiveness of communication assertiveness learning videos for Jambi University students. The data that will be collected in this research will be quantitative and qualitative data. Quantitative data is carried out using questionnaires which will be distributed to Jambi University students. The results of the research show that the material validation of the assertive communication skills learning video for PORKES students at Jambi University obtained a percentage of around 94.30% so that it could be declared eligible in the very good category. Media validation, the percentage of appropriateness in the assertive communication skills learning video was found to be around 94% in the very good category. The percentage of Jambi University PORKES student respondents through the Field Trial showed an average percentage figure of 86% with a very high classification of interest in learning in assertive communication skills. Based on the results of research that has carried out expert and field validation trials in developing Assertive Communication Skills Learning Videos for PORKES Students at Jambi University, it can be concluded that the development of learning media in this research began by conducting a need analysis on individuals aged 18-20 year.